Trade liberalization and female labor force participation: Evidence from Brazil - Isis Gaddis; Janneke Pieters (Institute for the Study of Labor (IZA), 2012)
While there is a large literature analyzing the distributional impacts of trade reforms across the income or skill distribution, very little is known about the gender effects of trade reforms. This paper seeks to fill this gap and investigates the impact of Brazil's 1987-1994 trade liberalization on labor force participation of women. To identify the causal effect of trade reforms we exploit exogenous variation in exposure to tariff reductions across states linked to spatial differences in states' initial industry composition. We find that tariff reductions were associated with an increase in female labor force participation and employment after a period of around two years. Our results are robust to a variety of different approaches in dealing with the potential endogeneity of regional exposure to trade liberalization, alternative measures of trade protection and different time periods. Moreover, we find evidence that employment flows across sectors, especially an accelerated shift from agriculture and manufacturing to trade and other services, but also greater labor market insecurity and male unemployment are behind the observed increase in female economic activity. This suggests that both push and pull factors induced women to join the labor force.
Keywords: F13; F16; J16; J21; O15; 330; female labor force participation; trade liberalization; Brazil